KAJIAN TEORITIS TENTANG AHLI WARIS PENGGANTI - Raisyah Putri Samosir; Wahyudianto; Muhammad Wahyudi (Jurnal At-Tabayyun, 2021)
In Islamic inheritance law, this is a new study and was not previously known by jurists in classical fiqh literature. This provision is a new breakthrough in terms of completing the inheritance of children (grandchildren) from heirs (fathers) who died earlier from the heirs (grandfathers), according to the jurists. The children’s school of thought is classified in the position of zaw al-arham according to the provisions of syara’ (in this case the Syafi’i fiqh) that a child (grandson) whose father dies earlier than the heir (grandfather) cannot obtain and receive an inheritance. This condition causes the orphan to suffer because of the loss of his father, as well as losing his right to inherit because his father’s relatives wear the hijab. Indeed, among the many cases there are several dispensations in which a grandfather bequeaths an orphan’s grandson. But often he died before doing it. Legislation in several Muslim countries no longer follows the classical school of fiqh rules which do not question the case in the rulings of their schools, but several changes have been made, especially regarding the rights of children whose father’s death precedes their grandfather’s. Islamic inheritance law in Indonesia contained in the KHI (Compilation of Islamic Law) has also introduced the existence of a substitute heir institution in terms of handling cases of children whose father’s death preceded their grandfather, as contained in article 185 which reads: a) Heirs who If he dies earlier than the heir, his position can be replaced by his son, except for those mentioned in Article 173, b) The share of the replacement heir may not exceed the share of the heir who is equal to the one being replaced.